Ethno-Safety Potential During the Polish-Ukrainian War for Halychyna in 1918 - Monolatii, Ivan (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
Modeling of the potential of the Western-Ukrainian People's Republic (WUPR) relying on modern theories and suggestions of politicians and geo-politicians is an important factor contributing to the study all the benefits and drawbacks the ethno-political sphere in question, as they show its security and geostrategic components. The author argues that within the proposed model of the potential of the WUPR it was the escalation from the stronger side (Poles), in particular, with the regard to the armaments escalation that was the most logical. It stood out in conditions of asymmetric imbalance: the weaker side (Ukrainians) shifted the “burden” of escalation to ideological and moral-ideological problems.